POLA KOMUNIKASI ANTARPERSONAL KONTRIBUTOR TELEVISI BERITA DENGAN STRINGER (STUDI KASUS PADA KONTRIBUTOR DAN STRINGER STASIUN TV SCTV DI KOTA BANDUNG) - Nazmi Abdurahman (CV. Lafadz Jaya, 2026)
Television, as an electronic mass medium, holds a strong appeal compared to other mass media due to its ability to present information in an audiovisual, up-to-date and engaging manner. Increasingly fierce competition within the television industry requires every news channel, including SCTV, to expand its information network to various regions through contributors. The limited reach of correspondents in covering vast areas has led to the emergence of the role of the stringer as a working partner who assists with reporting in the field. The working relationship between correspondents and stringers takes place within an informal organisation that relies heavily on the patterns of interpersonal communication established between them. This study aims to examine how the patterns of interpersonal communication established by SCTV news correspondents, in guiding their stringers to carry out reporting in the city of Bandung, by examining five aspects of interpersonal communication effectiveness according to DeVito’s humanistic approach, namely openness, empathy, supportiveness, positiveness and equality. This study employs a constructivist paradigm with a descriptive qualitative approach. Data were collected through observation, in-depth interviews, and documentation of SCTV’s Bandung Bureau correspondents and the stringers they collaborate with; these were subsequently analysed through data reduction, data presentation, and the drawing of conclusions, with validity tested using triangulation techniques. The results of the study indicate that the communication patterns established by contributors with their stringers operate both vertically and horizontally, characterised by openness in conveying instructions and information; empathy towards the stringers’ personal and professional circumstances; support in the form of training facilitation and solutions to field-based problems; a positive attitude evident in trust and work discipline; and equality in decision-making through democratic meeting forums. The interpersonal communication patterns established as a whole have proven effective in fostering work motivation, discipline, participation and the stringer’s enthusiasm in carrying out news reporting duties in the field.